Photonic Band Gap Material Topological Design at Specified Target Frequency. Issue 10 (4th June 2021) - Zhang, Xiaopeng; Luo, Yangjun; Yan, Yi; Liu, Pai; Kang, Zhan
Abstract: To achieve any specified band gap structure around target frequency, a new photonic crystals (PhC) topological design strategy is proposed. In the design optimization model, a band gap index that measures the minimal signed distances between the specified frequency and any two adjacent orders of frequencies is proposed, and the topology of PhC unit cell is represented with a low number of design variables through the material‐field series‐expansion. Then the sequential Kriging‐based algorithm is adopted for solving the multi‐peak and nondifferentiable optimization problems. Based on the numerical implementation of the proposed optimization method, the PhC unit cells are designed to provide band gaps precisely matching any specified central frequency value. The optimized unit cell designs are easily assembled to achieve a PhC device with the large relative band gap. Abstract : A new nongradient topology optimization method for maximizing the photonic crystals (PhC) band gap at any specified target frequency is proposed. Here, a minimal signed distances band gap index is first defined as the objective function. The material‐field series‐expansion model is employed for describing the PhC microstructural topology, and the optimization problem is solved with the sequential Kriging‐based optimization algorithm.